STUDI EFEKTIFITAS CONSTRUCTED WETLANDS FREE WATER SURFACE TANAMAN MELATI AIR (Echinodarus paleofolius) UNTUK MENURUNKAN KADAR PHOSPAT EFFLUENT IPAL RUMAH SAKIT KEN SARAS KABUPATEN SEMARANG - Fathurahman, Denny; Joko, Tri; Danudianti, Yusniar Hanani (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Hospital, as a public sevice provider, not only has a role in supporting health, but also in producing various pollutants which one of them wastewater as a result of the operational activity. Water Hyacinth ( Echinodarus paleofolius) is a water plant which is able to reduce and absorb the substances contained in wastewater. Therefore, the writer would like to use constructed wetlands type free water surface method to reduce phosphate level on effluent waste of the waste treatment installation at Ken Saras Hospital, Semarang Regency. The purpose of this research is to know the detention time effectivity of wastewater on constructed wetlands type free water surface using water hyacinth with consecutive detention time of 2, 4, 6 and 8 days. This research uses experiment method by using prestes- post test design. By using Shapiro Wilik’s data normality test and Krskal Wallis’s differentiating test. Based on Shapiro Wilik’s data normality test, the writer found p=0,001, so that the data are not normally distributed. While, by using Krskal Wallis’s differentiating test, the writer found the score of Asympsig : 0,001, so that it can be said that there are differences on the reduction of phosphate level before and after the treatment. The most effective detention time on this research is 4 days